2018
DOI: 10.3390/ijerph15040668
|View full text |Cite
|
Sign up to set email alerts
|

Association between Internet Gaming Disorder or Pathological Video-Game Use and Comorbid Psychopathology: A Comprehensive Review

Abstract: The addictive use of video games is recognized as a problem with clinical relevance and is included in international diagnostic manuals and classifications of diseases. The association between “Internet addiction” and mental health has been well documented across a range of investigations. However, a major drawback of these studies is that no controls have been placed on the type of Internet use investigated. The aim of this study is to review systematically the current literature in order to explore the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
267
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(305 citation statements)
references
References 92 publications
(258 reference statements)
25
267
0
13
Order By: Relevance
“…Discrepancies, however, may be due to the fact that moderator analyses were conducted on pooled within-group and controlled effect sizes and to the addition of the latest research results in our meta-analysis. Among these, the most commonly used approaches included family therapy, which in view of a variety of dysfunctional familial conditions (e.g., Schneider, King, & Delfabbro, 2017) appear beneficial not only for adolescent problematic internet gamers (e.g., , but also for adolescents with SUDs (for a review see Filges, Andersen, & Jørgensen, 2018). Similarly, mindfulness based programs successfully applied for ameliorating symptoms of IA and CB , and acceptance and commitment therapy implemented for the treatment of SA (e.g., have proven valuable to reduce symptoms of disordered gambling and SUDs (A-tjak et al, 2015;Li, Howard, Garland, McGovern, & Lazar, 2017;Maynard, Wilson, Labuzienski, & Whiting, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancies, however, may be due to the fact that moderator analyses were conducted on pooled within-group and controlled effect sizes and to the addition of the latest research results in our meta-analysis. Among these, the most commonly used approaches included family therapy, which in view of a variety of dysfunctional familial conditions (e.g., Schneider, King, & Delfabbro, 2017) appear beneficial not only for adolescent problematic internet gamers (e.g., , but also for adolescents with SUDs (for a review see Filges, Andersen, & Jørgensen, 2018). Similarly, mindfulness based programs successfully applied for ameliorating symptoms of IA and CB , and acceptance and commitment therapy implemented for the treatment of SA (e.g., have proven valuable to reduce symptoms of disordered gambling and SUDs (A-tjak et al, 2015;Li, Howard, Garland, McGovern, & Lazar, 2017;Maynard, Wilson, Labuzienski, & Whiting, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this consideration, some progress in the examination of neurobiological commonalities with SUDs has been achieved more recently within the domains of sex addiction (SA) and compulsive buying (CB) by analyzing phenomena traditionally investigated in SUDs such as conditioning processes (e.g., Hoffmann, Goodrich, Wilson, & Janssen, 2014;Snagowski, Laier, Duka, & Brand, 2016), cue reactivity, attentional bias and related neural network activation (e.g., Brand, Snagowski, Laier, & Maderwald, 2016;Gola et al, 2017;Jiang, Zhao, & Li, 2017;Laier, Pawlikowski, & Brand, 2014;Laier, Schulte, & Brand, 2013;Lawrence, Ciorciari, & Kyrios, 2014;Mechelmans et al, 2014;Pekal, Laier, Snagowski, Stark, & Brand, 2018;Schmidt et al, 2017;Seok & Sohn, 2015;Starcke, Schlereth, Domass, Sch€ oler, & Brand, 2012;Trotzke, Starcke, Pedersen, & Brand, 2014;Trotzke, Starcke, Pedersen, M€ uller, & Brand, 2015;Voon et al, 2014), or executive functioning (Derbyshire, Chamberlain, Odlaug, Schreiber, & Grant, 2014;Messina, Fuentes, Tavares, Abdo, & Scanavino, 2017;Raab, Elger, Neuner, & Weber, 2011;Trotzke et al, 2015). These studies demonstrated that among those conditions that have not yet been officially recognized in the DSM-5 as BAs, the currently available evidence regarding neurobiological indicators for parallels between substance-related and non substance-related behaviors mainly comes from the areas of IA, SA and CB, which are the focus of the present paper.…”
mentioning
confidence: 99%
“…In this context, the focus on gaming addiction has increased [17][18][19], with the inclusion of internet gaming disorder in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) in 2015 [20] and gaming disorder in the International Classification of Diseases and Related Health Problems (ICD-11) in 2018 [21]. In addition, the first studies on eSports performance have emerged, focusing mainly on the cognitive skills and challenges eSports players face [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As a case in point, a US telemedicine company recently announced positive results in a study of an action video game designed to treat attention deficit and hyperactivity disorder (ADHD), with plans to market it as a prescription digital therapy for ADHD (1). Meanwhile, several studies, including systematic reviews of comorbidity studies [(e.g., (2)(3)(4)], have shown a strong link between ADHD and Internet Gaming Disorder (IGD), suggesting that online gaming and other online activities may actually be a causal or contributing factor to developing ADHD. Similarly, a meta-analytic study showed that digital therapies for children and young people's mental health were promising (5), but also fueled anxieties in parents who could not reconcile encouraging their children to use the internet and games for treatment when they were constantly pressing them to reduce screen use, due to concern about the negative impact of digital media on children's emotional and social wellbeing (6,7).…”
Section: Introductionmentioning
confidence: 99%